2013
DOI: 10.1002/tox.21894
|View full text |Cite
|
Sign up to set email alerts
|

The crude extract ofCorni Fructusinhibits the migration and invasion of U-2 OS human osteosarcoma cells through the inhibition of matrix metalloproteinase-2/-9 by MAPK signaling

Abstract: Osteosarcoma is the most common primary malignancy of the bone cancers. In the Chinese population, the crude extract of Corni Fructus (CECF) has been used as Traditional Chinese medicine to treat several different diseases for hundreds of years. In the present study, effects of CECF on inhibition of migration and invasion in U-2 OS human osteosarcoma cells were examined. CECF significantly inhibited migration and invasion of U-2 OS human osteosarcoma cells. We also found that CECF inhibited activities of matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Using a type 2 DM model, this paper explored the role of PC on WT1 expression in glomeruli and the mechanism of PC on early nephropathy. We found that PC had the following effects: (1) it significantly reduced the FBG and elevated INS levels; (2) it had the effect of protecting against the renal damage, such as reducing the NAG and mALB levels, the renal morphology score and the kidney coefficient; and (3) it enhanced WT1 expression in glomerular podocytes. The findings indicated that PC had the effect of protecting early nephropathy in type 2 diabetic rats.…”
Section: Corni Fructus Components On Early Diabetic Nephropathy 545mentioning
confidence: 83%
“…Using a type 2 DM model, this paper explored the role of PC on WT1 expression in glomeruli and the mechanism of PC on early nephropathy. We found that PC had the following effects: (1) it significantly reduced the FBG and elevated INS levels; (2) it had the effect of protecting against the renal damage, such as reducing the NAG and mALB levels, the renal morphology score and the kidney coefficient; and (3) it enhanced WT1 expression in glomerular podocytes. The findings indicated that PC had the effect of protecting early nephropathy in type 2 diabetic rats.…”
Section: Corni Fructus Components On Early Diabetic Nephropathy 545mentioning
confidence: 83%
“…U‐2 OS cell line was purchased from the Food Industry Research and Development Institute (Hsinchu, Taiwan). Cells were cultured in 90% McCoy's 5A medium with 10% FBS, 2 mM L‐glutamine and antibiotics (100 Units/ml penicillin, and 100 μg/ml streptomycin) in a 75 cm 2 tissue culture flask at 37°C in a humidified atmosphere of 5% CO 2 …”
Section: Methodsmentioning
confidence: 99%
“…U‐2 OS cells (1.6 × 10 5 cells/well) were placed in a 12‐well plate for overnight then incubated with or without ouabain. Cells were collected, counted and stained with PI (5 μg/ml) and were analyzed using flow cytometer (BD Biosciences, FACS Calibur, San Jose, CA) assay for total viable cell number as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that oroxylin A could inhibit migration and invasion of human breast MDA-MB-435 cancer cells via the inhibition of MMP-2 and MMP-9 (11). Thus, MMP-2 and MMP-9 have been considered as targets in the development of drugs against tumor invasion and metastasis (12,13).…”
Section: Introductionmentioning
confidence: 98%